10 Segment Spiral Antenna to Measure Partial Discharge on High Voltage Equipment. Issue 1 (May 2021) - Laksono, Deni Tri; Laksono, Dedi Tri; Ulum, Miftachul; Oktavia Suzanti, Ika
Abstract: Electricity basically has become the main requirement for human beings on earth. Thus electrical reliability is the most important things so that electricity flow to consumers is not interrupted. The most electricity vital is substation, there are some disturbances that commonly occur in high voltage equipment in substation such as disruption due to old tool, interference due to human error, and natural disruption resulting in equipment damage. To minimize these disturbances we need a tool that can detect interference, namely sensors. One of disturbances in substations is Partial discharge. To find out a partial discharge in voltage equipment there are several ways such as measuring using a RC sensor detector and using an antenna. This study discusses partial discharge sensor that will detect the level of partial discharge that exists in high voltage equipment such as transformers, cables, GIS (Gas insulated switchgear) and others. Spiral antenna is the main topic in this research by making spiral antenna with 10 segments. The steps in making this antenna are firstly carried out design and simulation using CST 2018 software then implementing antenna on FR4 epoxy PCB. The antenna is tested for its characteristics based on several parameters such as VSWR, RL, and Bandwidth. This test is carried out using a VNA measurement tool. The test results show that this 10 segment spiral antenna produces a VSWR value of less than 2, an RL value of less than -15, and bandwidth included in signal frequency by partial discharge is around 300MHz - 3GHz.